A configuração espacial das ocupações criativas nos estados Sul brasileiros - Henrique, Jonas da Silva (2016)
The structure of this study is aimed at analyzing the spatial configuration of creative occupations in the southern states of Brazil, specifically in the discussion of the concept of creativity, innovation and Creative Economy, and guided by the guidelines of economic thought, providing an analytical framework, and examining the profile of the creative work and the dispersion or concentration in the regions of Parana, Santa Catarina and Rio Grande do Sul. The creative economy centers the human capital at the height of innovation fostered by sustainable ways in which creative productivity elaborates possibilities, products or services without stock or limit production. In view of these considerations this research uses the techniques of regional and spatial statistical analysis to evaluate the setting in space of creative occupations. The reference database is the Brazilian Census 2010, covering the characteristics of creative jobs and employers, and this analysis suggests the classification of creative workers; artistic, technical and technological. The creative occupations with a job, employers and self-employment gained prominence in the results obtained, and the dependence and influence over space showed the diversification of creative occupations, occurring mainly in peripheral regions. Participation in creative labor market is mostly in artistic occupations with greater territorial distribution jobs on their own, followed by technical occupations, with higher spatial similarity in jobs on their own and formal, technological occupations stood out in occupations with two or more jobs, especially in Rio Grande do Sul. The spatial clusters for creative diversification highlighted similarities in creative occupations with a job, employers, self-employed and total creative occupations. Thus, the diversification of creative occupations in a particular locality has a tendency to influence and overflowing local borders.